2009
DOI: 10.1161/strokeaha.108.532622
|View full text |Cite
|
Sign up to set email alerts
|

Expediting MRI-Based Proof-of-Concept Stroke Trials Using an Earlier Imaging End Point

Abstract: Background and Purpose-Before Phase III trials of acute stroke therapies, proof-of-concept MRI trials are increasingly used to gauge the likelihood of success. Given that animal models use infarct volume as the end point, Phase II trials have aimed to translate the findings using infarct growth. These trials could be expedited if subacute diffusion-weighted imaging lesion volume replaced late T2-weighted lesion volume as the primary end point. Methods-In the Echoplanar Imaging Thrombolytic Evaluation Trial, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…This finding raised the question of whether it was possible to predict this fixed stage as early as days [3][4][5][6]. Following this hypothesis, we found a good correlation between subacute and chronic volumes in line with previous work, 20,21 which nevertheless failed to take into account whether statistical conditions of a linear relationship were met for the full spectrum of volumes. Indeed, the estimation of FLAIR-3 was less efficient in the case of large volumes, resulting in a dispersion of the residuals.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding raised the question of whether it was possible to predict this fixed stage as early as days [3][4][5][6]. Following this hypothesis, we found a good correlation between subacute and chronic volumes in line with previous work, 20,21 which nevertheless failed to take into account whether statistical conditions of a linear relationship were met for the full spectrum of volumes. Indeed, the estimation of FLAIR-3 was less efficient in the case of large volumes, resulting in a dispersion of the residuals.…”
Section: Discussionsupporting
confidence: 82%
“…This result was in line with a subanalysis from the EPITHET population, which found the same prognostic value for subacute or chronic volumes in predicting day 90 NIHSS scores. 21 Here, we extended these data by choosing mRS, a global measurement of disability and handicap widely used in phase III trials, 17,18 instead of NIHSS, which is used to measure neurologic deficits and is not necessarily correlated with an individual's functional recovery. 16,30 The dataset used in this study presents some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Subacute DWI images scanned at days 3 through 5 have been previously reported to correlate well with final infarct volume. 15 Infarct growth was defined as the difference between the baseline DWI volume and final infarct volume. Five measures of infarct growth, which were the predefined efficacy end points in the EPITHET protocol, were assessed (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…28 Additionally, our study is based on calculation of infarct volume on DWI sequences in the acute setting within 72 hours of diagnosis. However, Ebinger et al 12 have shown that subacute reduced diffusion volume in adults tightly correlated with final neurologic outcome assessed with the National Institutes of Health Stroke Scale, but most studies have shown stable DWI lesion evolution from 36 hours to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9,10 Recent studies support infarct volume quantification as a potential tool in the pediatric population for predicting clinical outcome. [11][12][13] For example, Ganesan et al 14 observed that infarcts of Ͼ10% parenchymal volume on T2-weighted imaging were associated with poor outcomes. Additionally, Domi et al 15 reported…”
mentioning
confidence: 99%